Magneto-Structural Correlations in Coordination Polymers Based on Formate Ligand and Transition Metal Cations - Venegas-Yazigi, D; Venegas-Yazigi, D (American Chemical Society, 2025)
We present five three-dimensional (3D) coordination polymers (CPs) based on the formate ligand, [NaM(HCOO)3(H2O)]n with M = Co2+ and Ni2+ and [KM(HCOO)3]n with M = Mn2+, Co2+, and Ni2+, introducing three new nuclear structures with the P21 space group for [NaCo(HCOO)3(H2O)]n and [NaNi(HCOO)3(H2O)]n, and P6322 Sohncke SG with chiral nuclear structure for [KNi(HCOO)3]n, along two centric C2/c isomorphs [KMn(HCOO)3]n and [KCo(HCOO)3]n. Magnetic measurements indicate that antiferromagnetic interactions predominate in the five CPs, with averaged antiferromagnetic zJ/kB mean values from −1.18 to −94.9 K. Moreover, magnetic long-range order (LRO) at low temperatures is evidenced by the magnetic susceptibility and heat capacity measurements. Furthermore, single-crystal and powder neutron diffraction experiments were performed to elucidate the magnetic structure, confirming the antiferromagnetic ordering with possible spin canting, thus understanding these systems’ magnetic exchange pathway topology. © 2025 The Authors. Published by American Chemical Society.